การพัฒนาหลักสูตรฝึกอบรมเพื่อเสริมสร้างความสามารถในการจัดการเรียนรู้ ภาษาไทย ตามทฤษฎีเชื่อมโอนภาษา สำหรับครูที่สอนนักเรียนกลุ่มชาติพันธุ์: The Development of Training Curriculum to Enhance the Ability of Thai Language Teaching Based on Translanguaging Theory for the Teachers of Ethnic Group - Khaisaeng, Thitiporn; Jantakoon , Jakkr; Thamrongsottisakul , Wichian (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
The purpose of this research was to develop a training course to enhance the ability to organize learning thai according to the Translanguaging Theory for teachers teaching ethnic students by using research and development processes; conducting research in 4 steps: 1) to study the ability to manage learning Thai Based on the Translanguaging Theory linkage for teachers teaching ethnic students, 2) to establish and monitor the quality of training courses, 3) to test the use of training courses, and 4) to evaluate training courses. The target group consisted of 10 teachers, grade 3 students in schools under the Chiang Mai Primary Educational Service Area Office 6, who were obtained by using a specific selection method. The tools used include training courses to enhance the ability to manage learning Thai according to the Translanguaging Theory for teachers teaching ethnic students The statistics used are Stem test statistics using Wilcoxon markers, tee test statistics, and content analysis. The results showed that 1) teachers should have knowledge and understanding of standards and indicators in the Thai language learning subject curriculum, and be able to organize learning activities taking into account the differences of students; and the quality of training courses were examined. It was found that the curriculum components Overall, it was at a very suitable level ( = 4.46, S.D. - 0.55) and the course documentation. Overall, it was at a high level ( = 4.40, S.D. = 0.55). The training course was outstanding. The trainees received intellectual training from the prototype. 3) The results of the curriculum experiment revealed that the teachers who attended the training according to the curriculum had knowledge and understanding of Thai language learning management according to the Translanguaging Theory after training was significantly higher than before training at .05 and 4). At the highest level ( = 4.56, S.D. = 0.39), the process aspect towards the curriculum activities was at the high level ( = 4.48, S.D. = 0.39) and the outcome aspect on the application of the results obtained from the Training for teaching practice was at a high level ( = 4.32, S.D, = 0,50).